Structural basis of temperature-dependent electrical resistance of evaporation-deposited amorphous GeSe film - Shin, Sang Yeol; Golovchak, Roman; Lee, Suyoun; Cheong, Byung-ki; Jain, Himanshu; Choi, Yong Gyu (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
We employ EXAFS spectroscopy to refine the local atomic arrangements of evaporation-deposited equiatomic GeSe film. Amorphous structure of the as-deposited GeSe film turns out to satisfy mainly the 4:2 structural model. The crystallized GeSe film, however, consists of the orthorhombic GeSe crystals with the 3:3 atomic arrangements and quasi-crystalline Ge clusters. Its temperature-dependent electrical resistance is explained in connection with this structural difference, which exemplifies significance of the chemical environments on the electrical switching phenomena observed from amorphous chalcogenide solids. (C) 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: PHASE-CHANGE MATERIALS; ABSORPTION FINE-STRUCTURE; THIN-FILMS; OPTICAL-PROPERTIES; LOCAL-STRUCTURE; ALLOYS; MICROSCOPY; EXAFS